Developing a Robust Recombination Contact to Realize Monolithic Perovskite Tandems With Industrially Common p-Type Silicon Solar Cells - Hoye, Robert LZ (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
10.1109/JPHOTOV.2018.2820509